Combined measurement and QCD analysis of the inclusive e±p scattering cross sections at HERA - Aaron, Francisc Dionisie; Herbst, Matthew; Sauter, Michel David; Schöning, André; Schultz-Coulon, Hans-Christian (Journal of high energy physics, 2010)
A combination is presented of the inclusive deep inelastic cross sections measured by the H1 and ZEUS Collaborations in neutral and charged current unpolarised e±p scattering at HERA during the period 1994-2000. The data span six orders of magnitude in negative four-momentum-transfer squared, Q2, and in Bjorken x. The combination method used takes the correlations of systematic uncertainties into account, resulting in an improved accuracy. The combined data are the sole input in a NLO QCD analysis which determines a new set of parton distributions, HERAPDF1.0, with small experimental uncertainties. This set includes an estimate of the model and parametrisation uncertainties of the fit result.